Literasi Keuangan Syariah Dan Religiusitas Terhadap Perilaku Konsumtif Mahasiswa Generasi Z Dengan Variabel Mediasi Penggunaan Paylater - Clarisa Khotimatul Fitriyah; Rizky Nur Ayuningtyas Putri (Journal of Economic, Bussines and Accounting (COSTING), 2024)
This study aims to explore the influence of Sharia financial literacy and religiosity level on consumptive behavior, with the use of paylater as a mediating variable, among undergraduate students at UIN Raden Mas Said Surakarta. The purpose sampling method was employed in sample selection, with the Slovin model used to determine the sample size, which consisted of 100 students. Data analysis utilized Partial Least Squares (PLS) with the assistance of SmartPLS 3. The results indicate that Sharia financial literacy significantly affects consumptive behavior and the use of paylater. However, religiosity level does not significantly affect consumptive behavior and the use of paylater. On the other hand, the use of paylater significantly influences students' consumptive behavior. These findings highlight the importance of Sharia financial literacy in managing financial behavior, while religiosity level does not fully determine this aspect. Furthermore, the use of paylater can exacerbate consumptive behavior, indicating the need for better understanding of the financial implications of this payment option. Keywords: Islamic Financial Literacy, Religiosity, Consumptive Behavior, Paylater Usage.